2021
DOI: 10.1021/acsami.1c21901
|View full text |Cite
|
Sign up to set email alerts
|

Cell–Material Interactions in Direct Contact Culture of Endothelial Cells on Biodegradable Iron-Based Stents Fabricated by Laser Powder Bed Fusion and Impact of Ion Release

Abstract: Additive manufacturing is a promising technology for the fabrication of customized implants with complex geometry. The objective of this study was to investigate the initial cell−material interaction of degradable Fe-30Mn-1C-0.02S stent structures in comparison to conventional 316L as a reference, both processed by laser powder bed fusion. FeMn-based alloys have comparable mechanical properties with clinically applied AISI 316L for a corrosion-resistant stent material. Different corrosion stages of the as-buil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…Since, during degradation, the released ions react and form corrosion products, the consideration of the biocompatibility of single elements is not sufficient, and corrosion products generated in the complex environment of the living organism must be considered. Investigations of biocompatibility, even in vivo, consider the good biocompatibility of FeMn [ 13 , 19 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since, during degradation, the released ions react and form corrosion products, the consideration of the biocompatibility of single elements is not sufficient, and corrosion products generated in the complex environment of the living organism must be considered. Investigations of biocompatibility, even in vivo, consider the good biocompatibility of FeMn [ 13 , 19 , 27 , 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The released ions can form phosphates which deposit on the surface. Compounds with Fe and Mn are present on the surface, but the degradation can proceed further since exchange with the electrolyte is still possible [ 16 , 19 , 30 , 44 ]. In contrast, Ca-Phosphate (P), originating from the electrolyte, creates an inhibiting layer deteriorating the degradation rate [ 13 , 19 , 28 , 30 , 36 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the formed hydroxide (OH − ) ions interact with the Fe 2+ ions released into the solution, resulting in iron (II) hydroxide followed by the conversion to iron (III) hydroxide in the presence of water and air oxygen. Numerous Materials 2022, 15, 4900 2 of 14 studies on cytotoxicity and biocompatibility testify to the possibility of the use of Fe-based materials as biodegradable implants [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the absence of research dedicated to the manufacturing of NiTi Self-Adjusting Files by LPBF technology, it is worth mentioning alternative micro-scale devices that received increased attention. Several works were dedicated to the investigation of the feasibility of printing stents for coronary vessels from Co-Cr [ 18 ], titanium [ 11 ], steel [ 19 ], and NiTi [ 20 ], which previously were made using laser cutting methods from hollow tubes [ 21 ]. It was demonstrated that resolution, surface finish, and layer bonding dramatically impact the stent performance [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several works were dedicated to the investigation of the feasibility of printing stents for coronary vessels from Co-Cr [ 18 ], titanium [ 11 ], steel [ 19 ], and NiTi [ 20 ], which previously were made using laser cutting methods from hollow tubes [ 21 ]. It was demonstrated that resolution, surface finish, and layer bonding dramatically impact the stent performance [ 18 , 19 , 20 ]. In terms of Nickel-Titanium alloy, both superelasticity and shape memory effect are used for stents to decrease their volume during placement with subsequent extension under temperature influence and to impart a constant load on the walls of the vessel respectively.…”
Section: Introductionmentioning
confidence: 99%